Fast and green synthesis of battery-type nickel-cobalt phosphate (NxCyP) binder-free electrode for supercapattery - Gerard O. (Elsevier B.V., 2025)
Binder-free electrodes are increasingly important in energy storage technologies owing to the direct growth of active material on conducting substrates without binders, providing a shorter conduction channel for rapid electron transport. Various methods have been employed to synthesize binder-free electrodes, but most approaches often prove time-consuming, and some require elevated synthesis temperatures. Herein, a rapid and eco-friendly microwave-hydrothermal method was introduced to fabricate the battery-type nickel?cobalt phosphate (NxCyP) binder-free electrodes for supercapattery. The use of microwave accelerates heating and reduces the activation energy of the reaction, resulting in shorter synthesis time and lower reaction temperature. The NxCyP electrodes were fabricated at different parameters, such as temperature (90?200 C), time (5?20 min), and Ni:Co precursor ratios (4:0, 3:1, 2:2, 1:3, 0:4). The optimization study was carried out via Design Expert v13 software, and the optimized parameter was the temperature of 123.5 C, duration of 10.5 min, and Ni:Co of 2:2, namely N2C2P binder-free electrode. The N2C2P electrode exhibited larger flake- and flower-like morphologies, providing more space for electrolyte ion diffusion and a larger surface area for faradaic reactions. Consequently, it demonstrated outstanding electrochemical performance by displaying a high specific capacity (1699.7C/g at 3 mV/s), superior capacity retention, and the lowest resistances than other NxCyP electrodes. As a result, the N2C2P//AC supercapattery was created by merging it with an activated carbon (AC) electrode, showing a superior energy density (213.0 Wh/kg) and high electrochemical stability with 92.9 % retention after 3000 cycles at 10 A/g. ? 2024 Elsevier B.V.